Anthropometric markers of obesity and mortality in white and African American adults: The pennington center longitudinal study12. (20th June 2013) - Katzmarzyk, Peter T.; Mire, Emily; Bray, George A.; Greenway, Frank L.; Heymsfield, Steven B.; Bouchard, Claude
Abstract Objective: The purpose of this study was to determine the association between anthropometric measures of obesity and all‐cause mortality in white and African American men and women. Design and Methods: The sample included 14, 343 adults 18‐89 years of age. Height, weight, and waist and hip circumferences were measured, and the BMI (kg m−2), body adiposity index (BAI = ([hip circumference in centimeters]/[height in meters])1.5 – 18), waist‐to‐height ratio (WHtR) and waist‐to‐hip ratio (WHR) were computed. Vital status of the participants was determined from linkage with the National Death Index through 2009. Cox regression was used to assess the association between anthropometry and all‐cause mortality, adjusting for age, sex, year of baseline examination, study code, smoking status, alcohol consumption and physical activity. Hazard ratios (HR) are expressed per standard deviation of each variable. Results: A total of 438 deaths occurred during 120, 637 person‐years of follow‐up. All anthropometric markers demonstrated significant associations with all‐cause mortality in white subjects. In multivariable‐adjusted models, BMI (HR 1.34; 95% CI: 1.19‐1.50), waist circumference (1.41; 1.25‐1.60), BAI (1.34; 1.17‐1.53), WHtR (1.46; 1.28‐1.65), and WHR (1.40; 1.23‐1.61) all demonstrated significant relationships with mortality in white participants, but not in African Americans. In categorical analyses, there was a significant association between BMI status and mortality in whites but not African Americans. However, the risk associated with elevated waist circumference was similar in whites (1.49; 1.15‐1.94) and African Americans (1.60; 1.06‐2.40). Conclusion: In summary, this study has demonstrated race differences in the association between anthropometry and all‐cause mortality.